2009
DOI: 10.1111/j.1745-6592.2008.01215.x
|View full text |Cite
|
Sign up to set email alerts
|

A Compilation of Statistics for VOCs from Post‐1990 Indoor Air Concentration Studies in North American Residences Unaffected by Subsurface Vapor Intrusion

Abstract: This paper provides a summary of a number of indoor air quality studies reporting concentrations of volatile organic compounds (VOCs) in indoor air samples collected from residential properties in North America and provides average values for certain statistics (percentiles, detection frequency, maximum). This compilation includes several VOCs that are commonly assessed in studies of subsurface vapor intrusion to indoor air, but may also be attributable to consumer products, building materials, or even outdoor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 17 publications
4
47
0
Order By: Relevance
“…Our results are similar to those identified by the reviews done by Dawson and McAlary (2009), Koistinen et al(2008), and Loh et al(2007) with some distinct differences. Loh et al(2007) identified a similar subset of high priority VOC and SVOC chemical air pollutants using a combination of measurements and modeling.…”
Section: Summary Of Identified Hazardssupporting
confidence: 90%
See 1 more Smart Citation
“…Our results are similar to those identified by the reviews done by Dawson and McAlary (2009), Koistinen et al(2008), and Loh et al(2007) with some distinct differences. Loh et al(2007) identified a similar subset of high priority VOC and SVOC chemical air pollutants using a combination of measurements and modeling.…”
Section: Summary Of Identified Hazardssupporting
confidence: 90%
“…Our review identified a similar set of VOC and SVOC priority pollutants with the addition of acrolein, which was not included in their study. Dawson and McAlary (2009) identified benzene as a having an elevated cancer risks in most homes by comparing concentrations of a subset of 10 VOCs to available standards. Koistinen et al(2008) identified 5 priority pollutants in European homes, formaldehyde, CO, NO2, benzene, We also compared our results to an older review done by Brown et al(1994) to look at changes in concentrations over time.…”
Section: Summary Of Identified Hazardsmentioning
confidence: 99%
“…Figures 4a and b were prepared from the U.S. EPA VI database, selecting only those data meeting the criterion of falling below the 500 μg/m 3 cutoff. These data are compared with other published data from non-VI indoor air studies [27-31]. The results from Dawson and MacAlary [27] actually summarized some of the other datasets shown, but the individual results are given just to provide a sense that the summary captured well many other study results.…”
Section: Resultsmentioning
confidence: 96%
“…Indoor sources of VOCs are ubiquitous, resulting in detectable concentrations in indoor air that are often above regulatory screening levels. For example, background concentrations of TCE range from 0.3 to 1.6 µg/m 3 in houses unaffected by vapor intrusion (50 th to 95 th percentile values; Dawson and McAlary, 2009), concentrations that are the same level when compared to a residential 10 -6 risk limit of 0.43 µg/m 3 (USEPA, 2013). Background concentrations of TCE, benzene, and several other VOCs also commonly exceed regulatory screening levels (USEPA, 2011a).…”
Section: Regulatory Driversmentioning
confidence: 99%